GAMBARAN PENGETAHUAN IBU HAMIL TENTANG PERAWATAN PAYUDAYA PADA MASA KEHAMILAN DI BPM MARIAM PONTIANAK TAHUN 2020 - Tri Maharani (STIKES ADVAITA MEDIKA TABANAN, 2022)
Abstract : Breast care during pregnancy is an important part that must be considered during preparation for breastfeeding during pregnancy, the breast will swell and the area around the nipple will be darker in color. Therefore it is necessary to do breast care during pregnancy. The method used in this research is a descriptive method with a survey approach. The sampling technique of the researcher used the total sampling technique. This research was conducted on June 22-23 2020. The number of samples was 37 people. The research instrument used a questionnaire. Knowledge of pregnant women about breast care during pregnancy is less knowledgeable, as many as 30 respondents (81%). The knowledge of pregnant women about the purpose of breast care is lacking, as many as 21 respondents (57%). Knowledge of pregnant women about the benefits of breast care with sufficient knowledge is 19 respondents (51%). lack of knowledge about breast care as many as 35 respondents (95%). Keywords: Knowledge, Care, Breast, Pregnant